2018
DOI: 10.1051/matecconf/201816303001
|View full text |Cite
|
Sign up to set email alerts
|

Towards the utilization of waste glass powder in sustainable cement based overlays

Abstract: The article focuses on the possibility of utilizing waste glass powder in cement based overlays for sustainable construction. In the work, a study was carried out on the evaluation of the influence of waste glass powder, which modifies the overlay, on its adhesion to a concrete substrate. The waste glass powder was added in various amounts in relation to the binder mass. The adhesion tests were conducted using the commonly known pull-off method. The preliminary test results are presented and discussed in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Research has shown that using additions in the form of silica fume, metakaolin, short carbon fibers, polypropylene fiber, styrene/acrylic powder, magnesium phosphate, and fly ash for the cement mortar of the overlay is favorable in terms of the level of pull-off adhesion f b between the overlay and the concrete substrate [63][64][65][66][67][68][69][70][71][72][73]). In turn, using quartz and glass powder as an addition to the cement mortar of the overlay does not have a positive influence on the level of its pull-off adhesion f b [74,75]. Figure 16 presents the results of bonding strength tests with regards to the polypropylene fiber content in concrete.…”
Section: Modifications Of the Materials Of The Overlaymentioning
confidence: 99%
“…Research has shown that using additions in the form of silica fume, metakaolin, short carbon fibers, polypropylene fiber, styrene/acrylic powder, magnesium phosphate, and fly ash for the cement mortar of the overlay is favorable in terms of the level of pull-off adhesion f b between the overlay and the concrete substrate [63][64][65][66][67][68][69][70][71][72][73]). In turn, using quartz and glass powder as an addition to the cement mortar of the overlay does not have a positive influence on the level of its pull-off adhesion f b [74,75]. Figure 16 presents the results of bonding strength tests with regards to the polypropylene fiber content in concrete.…”
Section: Modifications Of the Materials Of The Overlaymentioning
confidence: 99%
“…This kind of industrial waste is a popular additive in concrete manufacturing [10]. The waste glass powder has been recently proposed to make overlays in the construction industry [14]. The aim of the research was to improve the mechanical properties of the coating, including its adhesion to the substrate, through the application of waste glass powder.…”
Section: Introductionmentioning
confidence: 99%